2007
DOI: 10.17221/2319-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Selenium content in tissues and meat quality in rabbits fed selenium yeast

Abstract: Ten weaned rabbits were fed a basal (control) diet containing 0.12 mg Se/kg. In 10 rabbits the basal diet was supplemented with Se-enriched yeast to increase the Se concentration to 0.50 mg/kg. Rabbits were slaughtered at the age of 11 weeks. Samples of meat, liver and hair of 4 rabbits from each group were taken and analyzed. No effect of Se on growth, feed conversion and dressing out percentage was observed. Loin and hindleg meat, liver and hair of control rabbits contained 93, 98, 521 and 267 μg Se/kg, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 14 publications
4
40
4
Order By: Relevance
“…This lack of effect of Zn on the Se content of rabbit meat may be due to the lower doses of Zn added to our feeds (200 mg/kg); however, differences between species should also be taken into account, because it seems that some proteins, for instance glutathione peroxidase, that depend on Se in other species (as chickens and humans) do not depend on Se in rabbits (De Blas and Wiseman, 1998). In fact, supplementing rabbit diets with higher doses of Se (0.5 mg/kg, added as Se-enriched yeast) than in our study, Dokoupilová et al (2007) encountered increases in the tissue Se content, but not in the activity of glutathione peroxidase. Further studies are needed to determine the different Se forms present in rabbits, and how they are absorbed, metabolized and affected by dietary factors, for instance by the different Se forms.…”
Section: Resultscontrasting
confidence: 65%
“…This lack of effect of Zn on the Se content of rabbit meat may be due to the lower doses of Zn added to our feeds (200 mg/kg); however, differences between species should also be taken into account, because it seems that some proteins, for instance glutathione peroxidase, that depend on Se in other species (as chickens and humans) do not depend on Se in rabbits (De Blas and Wiseman, 1998). In fact, supplementing rabbit diets with higher doses of Se (0.5 mg/kg, added as Se-enriched yeast) than in our study, Dokoupilová et al (2007) encountered increases in the tissue Se content, but not in the activity of glutathione peroxidase. Further studies are needed to determine the different Se forms present in rabbits, and how they are absorbed, metabolized and affected by dietary factors, for instance by the different Se forms.…”
Section: Resultscontrasting
confidence: 65%
“…The higher level of total lipids in the group administered PPB CCM7420 at the end of the experiment shows a long-term effect of bacteriocin on lipid resorption from the intestine and/or their utilization. The concentration of GSH-Px is often monitored in meat and other organs -liver, kidney in rabbits (Dokoupilová et al, 2007); studies concerning the serum level of GSH-Px enzyme and health status of rabbits are scarce. The measurement of the low activity of GSH-Px in experimental groups as well as the evidently good health of rabbits indicated that no oxidative stress was evoked during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Erdélyi et al (2000) observed that dietary Se supplementation with selenized yeast increased the activity of glutathione peroxidase (GSH-Px) in the blood and Se concentration in blood and liver. In the experiment by Dokoupilová et al (2007), the loin and hindleg meat of rabbits fed a diet supplemented with Seenriched yeast contained four times more Se than the meat of control rabbits. The purpose of this study was to evaluate the influence of different inorganic and organic forms of dietary Se on performance, Se deposition in meat, and meat oxidative stability in fattening rabbits.…”
Section: Introductionmentioning
confidence: 97%